2014
DOI: 10.1098/rspb.2014.0005
|View full text |Cite
|
Sign up to set email alerts
|

Demography can favour female-advantageous alleles

Abstract: When female fecundity is relatively independent of male abundance, while male reproduction is proportional to female abundance, females have a larger effect on population dynamics than males (i.e. female demographic dominance). This population dynamic phenomenon might not appear to influence evolution, because male and female genomes still contribute equally much to the next generation. However, here we examine two evolutionary scenarios to provide a proof of principle that spatial structure can make female de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
75
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(84 citation statements)
references
References 36 publications
8
75
1
Order By: Relevance
“…) have suggested that phenotypic plasticity in female behavior in response to rising temperatures is not sufficient to ameliorate the effects of climate warming. Furthermore, a recent study has demonstrated that local adaptation by TSD reptiles to climate is not always possible (Harts et al., in press).…”
Section: Discussionmentioning
confidence: 99%
“…) have suggested that phenotypic plasticity in female behavior in response to rising temperatures is not sufficient to ameliorate the effects of climate warming. Furthermore, a recent study has demonstrated that local adaptation by TSD reptiles to climate is not always possible (Harts et al., in press).…”
Section: Discussionmentioning
confidence: 99%
“…Resolving conflicts of interest in favour of female rather than male strategies should increase population growth [84]. This means that empowering women to pursue fitness-relevant goals is unlikely to explain demographic transitions towards lower fertility if these reproductive strategies are associated with lower long-term fitness [80,81].…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, genetic evolution of mate preferences might not be fast enough to prevent extinction if the fitness costs of heterospecific matings are high, as in the case for the species we have studied here. Finally, a recent theoretical study took a metapopulation ecological perspective and linked sexual selection to the evolution of plasticity and canalization [54]. This study is an empirical contribution to a much-needed integrative research programme of the consequences of sexual selection in heterogeneous environments [55].…”
Section: Discussionmentioning
confidence: 99%